Kerja Sama Kampus dan PKK dalam Pemberdayaan Masyarakat di Manggarai - Fransiska Widyawati (Randang Tana - Jurnal Pengabdian Masyarakat, 2021)
The PKK (Family Empowerment and Welfare) is a mass organization formed with the aim of empowering families to improve welfare, become more faithful, and devoted to God Almighty, have character and are virtuous, healthy and prosperous, advanced and independent, achieve gender equality and justice and legal and environmental awareness. To achieve this goal, PKK needs to collaborate with stakeholders in developing its strategic program. The campus is one of the important institutions as a supporting partner for the implementation of the PKK program. This article describes the collaboration between the Indonesian Catholic University of Santu Paulus Ruteng Campus and the Team (TP PKK) of Manggarai Regency, East Nusa Tenggara in developing community empowerment and education programs. The forms of campus support in the Manggarai Regency PKK program that have been implemented are: assistance in developing PKK strategic programs, Education and Socialization of the PKK role to the District PKK TP and holding joint webinars to educate the wider community. The target of this activity is the District PKK TP, the District PKK TP, the Kelurahan/Village PKK TP and the Manggarai community in general. The activities that have been carried out have had a positive impact in the form of changes in knowledge, behavior and the establishment of mutual cooperation. Therefore, it is recommended that these activities be carried out regularly and continuously in the future and need to be expanded to other fields